Transport Matters : Integrated Approaches to Planning City-Regions. - Hull, Angela (RTPI Library Series, 2010)
Addressing the principles of sustainability, spatial planning, integration, governance and accessibility of transport, this book focuses on the key social problems of the twenty-first century: efficient and low energy transport systems which serve the needs of everybody.